The Effect of Local Revenue, Fiscal Decentralization, and Fiscal Stress on Government Financial Performance - Nyoman Ayu Wulan Trisna Dewi; Ni Luh Putu Dita Silviani; Ni Kadek Meila Anggraeni (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of local revenue, fiscal decentralization and fiscal stress on the financial performance of local governments in Badung Regency. The type of data used in this study is secondary data of Badung Regency APBD data with a span of 3 years (2017-2019). This research is quantitative research by paying attention to the causal relationship (causal effect). The results of this study indicate that local revenue and fiscal stress does not have a positive effect on the financial performance. Fiscal decentralization has a significant negatif effect on the financial performance of local governments.